Approaching obsolescence? A multi-criteria analysis of high-risk dams in the United States Pacific Northwest. Issue 2 (4th March 2022) - Nagel, Alexander C.; Ptak, Thomas
ABSTRACT: This research uses a multi-criteria analysis tool and field site observation to critically analyse a network of dams across a single watershed in the US Pacific Northwest. The analysis offers a template to better understand some nuances and complexities involved in decision-making leading to relicensing, retrofitting or decommissioning of both powered and non-powered structures. The study focuses on 13 dams in Oregon's Willamette River Basin Reservoir System, where the average age of structures is 62 years, exceeding a national mean of 57 years. Research outcomes can inform stakeholders who make decisions regarding America's high-risk dam network as it rapidly approaches obsolescence.